The Evaluation of higher education systems - Cowen, Robert (World yearbook of education, 1996)
Presents an evaluation of the following countries: Algeria, Australia, Brazil, Canada, People's Republic of China, France, Hong Kong, Japan, Republic of Korea, United States, United Kingdom, Latin America.